MAIN DIRECTIONS OF SOCIAL TRANSFORMATION - Qurbonov Tohir Hamdamovich (Western European Studies, 2025)
The article analyzes the processes of social transformation and the role of scientific knowledge in this. On a scientific basis, the concept of transformation and its various interpretations, constructive and destructive directions, socio-cultural transformation, cybernetic approaches, "knowledge society", "knowledge economy", "information society" are revealed.
Keywords: approaches; knowledge society; knowledge economy